UJI AKTIVITAS SENYAWA TURUNAN TERPENOID, STEROID DAN FENOLIK DARI EKSTRAK JARINGAN KAYU BATANG TUMBUHAN NDOKULO (Kleinhovia hospitaL.) TERHADAP PERTUMBUHAN SEL KANKER (Leukemia P-388) - Nurhidayah, Nurhidayah; Minarti, Minarti; Pratama, Anugrah; Imran, Imran (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Research on this activity test aiming to determine the bioactivity and toxicity properties of compounds derived terpenoids, steroids and phenolic heartwood of plant tissue extracts Ndokulo (Kleinhovia hospita L.) on the growth of cancer cells (leukemia P-388). The method used is, sampling plant stem of Ndokulo, preparation, maceration, evaporation, extraction, fractionation, and activity test against Artemia salina and cancer cell. The main Component from n-hexane extract of the heartwood of this plant is Î²-sitosterol compound. The test against A. salina has the same tendency as the test of murine leukemia cells P-388 so that the primary test to measure the toxicity of the sample A. salina is proportional to the secondary test by measuring sample cytotoxicity against murine leukemia cells P-388. The measurements showed that the extracts have bioactivity against Artemia salina and potentially inhibit cancer cells growth.Â Keywords : Terpenoids, steroids, phenolic,Â artemia salina, leukemia P-388.